Cultural processes in Donbass region during the Second World War: historiographical discourse - Yevgeniіa Protsenko (Cхід, 2018)
The article is devoted to the discourse of historiography of cultural processes in the Donbass during the Second World War. The author analyzes the works of Soviet, Ukrainian and foreign historians on the topic. An essential feature of all the scientific research results of the Soviet period was the apologetics of the role of the Communist Party in cultural construction in Ukraine. At the same time, one can not deny the value of the scientific achievements of Soviet scholars who laid the foundations of modern Ukrainian historiography of the Second World War. With the achievement of Ukraine's independence, an attempt was made to broaden the research issues, in particular to characterize the dynamics of cultural processes during the war years. The researchers carried out significant work on the accumulation of material on certain aspects of cultural development, both in Ukraine and in Donbass in particular. Modern Ukrainian studies still have stereotypes, poorly studied regional studies, the topic of cramped memory, trauma, politics, psychological aspects of the war. Foreign historiography is important for a methodological and conceptual point of view, but scientific publication are deprived of materials from Ukrainian archives. Consequently, cultural processes in the Donbas during the Second World War did not become the subject of scientific research and require further consideration.